Screening of diabetic nephropathy patients prone to triggering factors of diabetic foot - Regina Coeli Vasques de Miranda Burneiko; Susimary Aparecida Trevizan Padulla; Cristina Elena Prado Teles Fregonesi; Marcela Regina de Camargo; Andréa Jeanne Lourenço Nozabieli (Universidade de Fortaleza, 2010)
Objective: To survey the prevalence of diabetic paients in the hemodialysis unit, screening those prone to outbreak of neuropathy and signs and symptoms of diabetic foot. Methods: We conducted a survey of the number of diabetics in a hemodialysis unit to apply the Michigan Neuropathy Screening Instrument Questionnaire in order to screen subjects with signs of sensory loss. Also, we observed variables related to the magnitude of the disease. The subjects were divided into two groups: Group A, no sensory deficit with a score of less than five and Group B with sensitive deficit with a score greater than or equal to six. Group B was submitted to examination, muscle strength testing, nerve palpation, and sensitivity testing of the feet. We applied the Mann-Whitney test to verify differences between groups (p <0.05). Results: Of the 168 participants of dialysis, 37 (22.02%) were diabetic and of these 34 (20.24%) joined in the study. To characterize the group B (n = 20), we did a frequency distribution and 4 (20%) presented alterations related to nerve palpation, 11 (55%) regarding muscle strength, 17 (85%) to sensitivity testing, 11 (55%) had neuropathy, 6 (30%) had plantar ulcers, 4 (20%) amputations and 100% were unaware of the diabetic foot syndrome. Conclusions: There was considerable percentage of diabetics in the hemodialysis unit, and more than half of them showed signs of neuropathy, decreased muscle strength and at least one of the signs and symptoms of diabetic foot.